Consolation in Philippians : philosophical sources and rhetorical strategy - Holloway, Paul A., 1955- (Monograph series (Society for New Testament Studies), 2001)
In this rhetorical-critical study Holloway puts Paul's letter in the context of ancient theories and literary practices of 'consolation' and argues that Paul wrote to the Philippians in order to console them.